Digital Innovations and Policy Mechanisms in Financing Farmers’ Working Capital: Insights from Dhule District - Deepak Suklal Pawar, Rajendra Sinha (Journal of Informatics Education and Research, 2025)
Agriculture remains the backbone of India’s rural economy, with farmers relying heavily on timely and affordable credit to sustain operations. Working capital finance, which covers recurring expenses such as seeds, fertilizers, irrigation, and labor, has historically been accessed through informal credit channels, creating cycles of debt and financial vulnerability. In recent years, however, digital innovations such as mobile banking, Unified Payments Interface (UPI), Aadhaar-enabled payment systems, and digital Kisan Credit Cards have emerged as transformative tools for agricultural finance. Alongside these, institutional mechanisms designed by NABARD and policies of the Central and State governments aim to provide structured and affordable working capital solutions to farmers. This study investigates the convergence of digital innovations and policy mechanisms in financing farmers’ working capital, with specific reference to the Dhule District of Maharashtra. The research employs a descriptive design, collecting primary data from 419 farmers across four talukas (Dhule, Shindkheda, Sakri, and Shirpur) through structured questionnaires, supplemented by qualitative interviews with 55 officials from NABARD, banks, and Panchayat Raj institutions. Statistical tests, including ANOVA, Chi-Square, Correlation, and Regression, are applied using SPSS 25 to evaluate hypotheses on the impact of digital innovations, awareness of government schemes, and the combined effect of both on the sustainability of agricultural finance. Findings highlight that digital innovations significantly enhance efficiency in working capital management, awareness of government schemes strongly influences adoption, and integration of technology with policy frameworks substantially improves sustainability. The study offers critical insights into modernizing rural finance, strengthening farmer resilience, and promoting sustainable agricultural development in India.